The effect of park renovation on civic trust: a survey experiment approach. Issue 6 (2nd November 2019) - Potter, Alan; Sadin, Meredith L.
ABSTRACT: While urban planners often cite public park revitalization as a means of improving community civic trust, there is limited research that verifies this practice. To address this gap, this study utilizes a survey experiment with Miami-Dade County residents living near a park undergoing renovation. The study finds that informing people about the renovation can increase civic trust relative to not informing them. The benefits of this research are twofold: the survey experiment methodology serves as a cost-effective means of comparing design elements while the findings confirm and extend conventional wisdom regarding the effect of park revitalization on civic trust.